Changes in Microbiota Profiles After Prolonged Frozen Storage of Stool Suspensions - Dorsaz, Stéphane; Charretier, Yannick; Girard, Myriam; Gaïa, Nadia; Leo, Stefano; Schrenzel, Jacques; Harbarth, Stephan; Huttner, Benedikt; Lazarevic, Vladimir (Frontiers in Cellular and Infection Microbiology, 2020)
Introduction: Fecal microbiota transplantation (FMT) is recommended as safe and effective treatment for recurrent Clostridioides difficile infections. Freezing the FMT preparation simplifies the process, allowing a single stool sample to be used for multiple receivers and over an extended period of time. We aimed to assess the effect of long-term frozen storage on bacterial taxonomic profiles of a stool suspension prepared for FMT. Methods: DNA was extracted from a stool suspension before freezing and sequentially during the 18-month storage period at −80°C. Two different protocols were used for DNA extraction. The first relied on a classical mechanical and chemical cell disruption to extract both intra- and extracellular DNA; the second included specific pre-treatments aimed at removing free DNA and DNA from human and damaged bacterial cells. Taxonomic profiling of bacterial communities was performed by sequencing of V3–V4 16S rRNA gene amplicons. Results: Microbiota profiles obtained by whole DNA extraction procedure remained relatively stable during frozen storage. When DNA extraction procedure included specific pre-treatments, microbiota similarity between fresh and frozen samples progressively decreased with longer frozen storage times; notably, the abundance of Bacteroidetes decreased in a storage duration-dependent manner. The abundance of Firmicutes, the main butyrate producers in the colon, were not much affected by frozen storage for up to 1 year. Conclusion: Our data show that metataxonomic analysis of frozen stool suspensions subjected to specific pre-treatments prior to DNA extractions might provide an interesting indication of bacterial resistance to stress conditions and thus of chances of survival in FMT recipients.